Green bond standards as a way to reduce information asymmetry - Aftowicz, Agata (Journal of Finance and Financial Law, 2025)
The purpose of the article. The purpose of the article is to systematize knowledge in the field of green bond standards as well as examine the differences between the most popular of them. The aim is to question whether the requirements of individual standards actually reduce information asymmetry on the part of investors in the market. Methodology. The texts of the 5 most popular green bond standards in the world were analyzed and were compared with each other, outlining the 5 most important categories in the context of information asymmetry, according to the author. The work contains the comparison of the standards and identifies the differences between them. Results of the research. The results of the research can be summarized as follows. The conducted research allowed for the identification of differences between individual standards and the assessment of whether these differences have a significant impact on the asymmetry of information in the green bond market. The study results show that green bond standards are not an ideal way to reduce the negative effects of information asymmetry in the market. The study shows the need to standardize the requirements for issuers who want to have a certificate that is an actual confirmation of high-quality green bonds in order to eliminate information asymmetry in the market.